RANCANG BANGUN SISTEM INFORMASI MONITORING KEHADIRAN MAHASISWA MENGGUNAKAN TEKNOLOGI RFID BERBASIS WEBSITE TERINTEGRASI SPREADSHEET - Yoli Andi Rozzi; Venny Novita Sari (JUTIM (Jurnal Teknik Informatika Musirawas), 2026)
Student attendance is one of the important data in academic activities because it can be used to monitor participation, discipline, and lecture activities. However, attendance recording that is still carried out manually has several weaknesses, such as requiring more recording time, being prone to data errors, being difficult to recapitulate, and having the potential for attendance manipulation. This study aims to design and develop a student attendance monitoring information system using RFID technology based on a website integrated with a spreadsheet. The research method used is Research and Development (R&D) with a prototyping approach. The developed system uses the RC522 RFID Reader as the card reader, NodeMCU ESP8266 as the main controller, LCD I2C and buzzer as indicators, Google Apps Script as the data connector, and Google Spreadsheet as the storage and monitoring medium for attendance data. The test results show that the system is able to read RFID cards, display attendance status, distinguish between check-in and check-out status, and send attendance data to Google Spreadsheet in real time. This system can support the attendance process to become faster, more structured, and easier to monitor by lecturers or administrators. Therefore, the developed system can be used as an alternative solution to support the digitalization of student attendance management in higher education.